The expedient of the argumentation in the journalism of Eliane brum: analysis of her columns to el país brasil - Vivar, Jesús Miguel Flores (2018)
This article is devoted to analyzing the narrativedynamics of Eliane Brum as a columnist in the digitalenvironment, aiming to highlight the characteristicvalues of her writings, woven under the argumentationprocess, in the El País Brazil portal. To do so, itdevelops a qualitative study of her texts most accessedby readers in 2016, based on a data collection carriedout with the journal’s management, to identifyconciliations between Brum’s journalistic practice andthe complex-comprehensive epistemology proposedby Künsch.